2018
DOI: 10.3389/fphar.2018.01358
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities of Nanotechnology as Delivery Platform for Tocotrienols in Cancer Therapy

Abstract: Plant-derived phytonutrients have emerged as health enhancers. Tocotrienols from the vitamin E family gained high attention in recent years due to their multi-targeted biological properties, including lipid-lowering, neuroprotection, anti-inflammatory, antioxidant, and anticancer effects. Despite well-defined mechanism of action as an anti-cancer agent, their clinical use is hampered by poor pharmacokinetic profile and low oral bioavailability. Delivery systems based on nanotechnology were proven to be advanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 64 publications
0
31
0
4
Order By: Relevance
“…It is noteworthy that subsequent in vivo and clinical studies using beta-T3 will require specific delivery systems as previously suggested for tocotrienols. As reported by Maniam et al, the use of tocotrienols is hampered by their lower bioavailability, solubility, and poor pharmacokinetic profile when compared to tocopherols [87,88]. Despite the fact that oral T3s have better bioavailability in rats than intramuscular and intra-peritoneal routes of administration, this bioavailability couldn't exceed more than 28% in the case of alpha-T3, and not more than 9% for γand δ-tocotrienols [59,89].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that subsequent in vivo and clinical studies using beta-T3 will require specific delivery systems as previously suggested for tocotrienols. As reported by Maniam et al, the use of tocotrienols is hampered by their lower bioavailability, solubility, and poor pharmacokinetic profile when compared to tocopherols [87,88]. Despite the fact that oral T3s have better bioavailability in rats than intramuscular and intra-peritoneal routes of administration, this bioavailability couldn't exceed more than 28% in the case of alpha-T3, and not more than 9% for γand δ-tocotrienols [59,89].…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome these challenges, nanotechnology delivery tools were developed to improve tocotrienols efficacy in vivo. Using nano-formulations (tumor-targeted nano-carriers) in animal models, tocotrienols exhibited a 10-fold higher anti-proliferative effect and resulted in up to 60% of tumor regression [87]. Thus, improving tocotrienols, especially beta-T3 s, bio-absorption and access to tumor cells through nanotechnology bio-systems, will provide an enhanced therapeutic effect than usual delivery routes.…”
Section: Discussionmentioning
confidence: 99%
“…By reducing the dose of gemcitabine, we can potentially reduce the toxicities associated by gemcitabine [53][54][55]. Nanotechnology in formulation, such as niosomes or liposomes, may be able to co-deliver SN extract and gemcitabine together [56]. These studies supported that SN extracts could be used to potentiate a chemotherapy, and are worth further investigation.…”
Section: Discussionmentioning
confidence: 80%
“…The production of various nanoformulations such as niosomes, liposomes, and polymeric nanoparticles, require high energy for its processing so that they can overcome stability related challenges such as coalescence and creaming (Maniam et al, 2018). Generally, nanoformulations are produced by either of the two processes that are top to bottom (pulverization, micronization) or bottom to top approach (nucleation).…”
Section: Challenges Aheadmentioning
confidence: 99%